2006
DOI: 10.1161/01.str.0000221783.08037.a9
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol Protects Against Brain White Matter Damage and Cognitive Impairment in a Rat Model of Chronic Cerebral Hypoperfusion

Abstract: Background and Purpose-White matter lesions contribute to cognitive impairment in poststroke patients. The present study was designed to assess the neuroprotective mechanisms of cilostazol, a potent inhibitor of type III phosphodiesterase, through signaling pathways that lead to activation of transcription factor cAMP-responsive element binding protein (CREB) phosphorylation using rat chronic cerebral hypoperfusion model. Methods-Rats underwent bilateral common carotid artery ligation. They were divided into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(97 citation statements)
references
References 20 publications
6
91
0
Order By: Relevance
“…In this study, two different strains (Wistar and SD) of rats were used to investigate the pathophysiology of VaD. By convention, Wistar rats are used to study the white matter lesions that can result from chronic cerebral hypoperfusion associated with BCCAO (Nakaji et al, 2006;Watanabe et al, 2006), and SD rats are used as a model for BCCAO-associated hippocampal neuronal damage and cognitive impairment (Pappas et al, 1996;Farkas et al, 2006;Liu et al, 2007). However, to date, the reason why these different strains of rats exhibit different histological pathology due to chronic cerebral hypoperfusion has been unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, two different strains (Wistar and SD) of rats were used to investigate the pathophysiology of VaD. By convention, Wistar rats are used to study the white matter lesions that can result from chronic cerebral hypoperfusion associated with BCCAO (Nakaji et al, 2006;Watanabe et al, 2006), and SD rats are used as a model for BCCAO-associated hippocampal neuronal damage and cognitive impairment (Pappas et al, 1996;Farkas et al, 2006;Liu et al, 2007). However, to date, the reason why these different strains of rats exhibit different histological pathology due to chronic cerebral hypoperfusion has been unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, the reason why different strains of rats are used to study various aspects of chronic cerebral hypoperfusion has remained obscure. Wistar rats have been used to investigate BCCAO-induced white matter lesions (Nakaji et al, 2006;Watanabe et al, 2006), whereas Sprague-Dawley (SD) rats have been adopted to evaluate the hippocampal neuronal damage and cognitive impairment after BCCAO (Pappas et al, 1996;Farkas et al, 2006;Liu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This may represent a beneficial effect of clopidogrel on cerebrovascular endothelium as reported in the second Trial of Cilostazol in Symptomatic Intracranial Arterial Stenosis (TOSS 2) study for preventing intracranial atherosclerotic progression. 17 Previous studies have shown that cilostazol increases rCBF in a rat model of chronic cerebral hypoperfusion, 18,19 and that cilostazol improves rCBF in the penumbral region in a rat model of middle cerebral artery occlusion. 20 In clinical studies, cilostazol also increases rCBF compared with ticlopidine at the chronic stage of cerebral infarction with a vasodilating effect.…”
Section: Omote Et Al Pleiotropic Effect Of Cilostazol In Shr-spmentioning
confidence: 99%
“…The rat model of BCCAO shows marked white matter rarefaction and glial cell activation (Wakita et al, 1994(Wakita et al, , 1998. WM lesions are thought to contribute to cognitive impairment, and they have a strong relationship with oxidative stress, apoptosis and inflammatory damage (Wakita et al, 1994;Tanaka et al, 2001;Watanabe et al, 2006).…”
mentioning
confidence: 99%